Sistem Kontrol dan Monitoring Kualitas Air Tambak Udang Windu Dengan Metode Fuzzy Logic Control Menggunakan Mikrokontroler NI myRIO - Ayu Samura; Wijaya Kurniawan; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The water quality is a very important factor for the survival and productivity of shrimp farming. The water quality can be seen from the physical parameters of water temperature, salinity, and turbidity . Poor water quality can lead to decreased appetite of shrimp, slow fattening, and susceptible to disease. To avoid these problems, the authors propose an embedded system that can monitoring and controlling the shrimp farm water quality based on temperature, salinity and water turbidity parameters.Microcontroller NI myRIO-1900 with fuzzy logic controller methode are used to control and monitor the water quality of shrimp farm. This sistem can also store the results of monitoring and controlling data that has been done. Based on the test, the sistem can monitor the temperature, salinity and turbidity with an average time stable 241.67 seconds. For determination the shrimp farm water quality using Fuzzy Logic Controller method with three membership and five membership compared to manual calculation obtained fuzzy result with five membership is much more accurate with difference 0.51, while fuzzy with three membership yield difference 3.22. on the water quality control function by controlling the speed of the pump rotation produce a good level conformity.